Sistemas de la democracia sustentable = Sustainable Democracy Systems - García Lirios, Cruz; Montero y López-Lena, María; Marcos Bustos Aguayo, José; Carreón Guillén, Javier; Hernández Valdés, Jorge (Comunitania. Revista Internacional de Trabajo Social y Ciencias Sociales, 2012)
The present test must like objective compare the coercive political systems with the persuasive political systems. For such intention, the differences between the authoritarianisms, totalitarianism, presidential and parliamentarian are resisted. Once established an evolutionary line of the political systems that go of the coercion to the persuasion, the present test raises a new anchored persuasive political system to the foundations of the presidential. Sustainable Presidential Politic System (SPPS) which would have its distinctive process in the fight, the debate and the election of representatives. Unlike other democracies, the SPPS would have a regulating power of the differences between the executive, legislative and the judicial one. In such sense, the political platforms and proselytisms would be determined by problematic the environmental ones that they prevent the viable development. The discussion of the SPPS will open the discussion regarding the public agenda, the ecological problems and the relation between the academy and political class. El presente ensayo tiene como objetivo comparar los sistemas políticos coercitivos con los sistemas políticos persuasivos. Para tal propósito, se contrastan las diferencias entre los autoritarismos, totalitarismo, presidencialismos y parlamentarismos. Una vez establecida una línea evolutiva de los sistemas políticos que va de la coerción a la persuasión, el presente ensayo plantea un nuevo sistema político persuasivo anclado a los fundamentos del presidencialismo. Se trata del Sistema Político Presidencial Sustentable (SPPS) el cual tendría su proceso definitorio en la contienda, el debate y la elección de representantes. A diferencia de otras democracias, el SPPS tendría un poder regulador de las diferencias entre el ejecutivo, el legislativo y el judicial. En tal sentido, las plataformas y los proselitismos políticos estarían determinados por las problemáticas ambientales que impiden el desarrollo sustentable. La discusión del SPPS abrirá la discusión relativa a la agenda pública, los problemas ecológicos y la relación entre la academia y clase política.